Health professionals' inclusion of green space in the management of long term conditions: a scoping review. (21st October 2020) - Buckley, Amy; Brownlie, Karl; Hill, Karl; Hallamore, Ruby-Rose; Vijan, Nikita; Perry, Meredith
Abstract: Background: Green space intervention, enabling participation in activities of importance, as a component of a supported self-management could reduce the burden on individuals with long term health conditions (LTC) and the health-care system. Objectives: The primary aim of this scoping review was to explore evidence of health professionals' (HPs) use of green space within supported self-management or active intervention for people with LTC. Methods: Major electronic databases were searched since inception until February 2020. Studies including HP prescription of green-space as part of supported self-management were included. Results: The initial search found 3 eligible studies, however to widen the scope of research we removed an exclusion criteria which resulted in an additional 5 studies. Interventions using parks, gardens, forest/woodlands and wetlands resulted in improved psychological, physical and social wellbeing for people with LTC. There was limited, low levels of evidence for HP prescription of green space for supported self-management of people living with LTC. Conclusions: Studies demonstrated improvements in wellbeing across multiple constructs (physical, psychological and social) in people with LTC, thus green space may be an important person-centered inclusion of supported self-management. Further evidence demonstrating the effectiveness of green space for supported self-management is required alongside research exploring the risks associated with green space prescriptions for people with LTC.